HUBUNGAN PENGETAHUAN REMAJA PUTRI KELAS X TENTANG ABORTUS PROVOKATUS DENGAN SIKAP REMAJADALAM PENCEGAHAN ABORTUS PROVOKATUS DI SMK NEGERI 3 PANYABUNGAN KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL TAHUN 2016 - Batubara, Novita Sari; Harahap, Aldina (Universitas Aufa Royhan, 2016)
Social and cultural environment that is not positive is a risk factor for teens to get caught up in sex behavior. Sex behavior in adolescents do have extended a long line of teenage pregnancy out of wedlock. Most choose to abort, not a few who mambesarkan womb and dumped the baby after birth.The purpose of this study to determine the relationship of class X girls knowledge about abortion provokatus with adolescent attitude in the prevention bortus provokatus SMK Negeri 3 Panyabungan Kecamatan Panyabungan Kabupaten Mandailing Natal District of the Year 2016. This research was descriptive correlation with cross sectional design. Polulasi in this study entire class X girls were 72 people sampling technique using total sampling measuring instrument used was a questionnaire. The statistical test using chi square.Based on the above table the majority of respondents who have a good knowledge of as many as 17 respondents (23.6%). Based on statistical tests performed, namely p value = 0.000. Based on the decision made is when the p value <0.05 with 95% confidence level, the Ha accepted which means there is a relationship between the Young Women Class X Knowledge about abortion provokatus with attitude Teens in Prevention abortion provokatus at SMK Negeri 3 Panyabungan District of Panyabungan Mandailing Christmas 2016.Based on the results, discussion, conclusions that researchers take on this research in order to gain knowledge about abortion provokatus, for the respondents expected a lot more to add insight about abortion provokatus by reading or following health education about abortion provokatus in health center or clinic midwife.